2022
DOI: 10.1002/smll.202106937
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healable and Stretchable Ionic‐Liquid‐Based Thermoelectric Composites with High Ionic Seebeck Coefficient

Abstract: The advancement of wearable electronics, particularly self‐powered wearable electronic devices, necessitates the development of efficient energy conversion technologies with flexible mechanical properties. Recently, ionic thermoelectric (TE) materials have attracted great attention because of their enormous thermopower, which can operate capacitors or supercapacitors by harvesting low‐grade heat. This study presents self‐healable, stretchable, and flexible ionic TE composites comprising an ionic liquid (IL), 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 61 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…31 For instance, Akbar et al reported an ionogel with excellent heat-induced self-healability by incorporating ion-dipole interactions into the system. 32 Dang et al utilized dynamic disulfide bonds to promote the reconstruction of the polymer network, resulting in the excellent and efficient self-healing performance of the ionogel, which guarantees the ionic conductor suitable for various functional applications. 33 The unique properties of ILs endow ionogel-based flexible sensors with advantages of chemical and thermodynamic stabilities, nonflammability, nonvolatility and high ionic conductivity.…”
Section: New Conceptsmentioning
confidence: 99%
“…31 For instance, Akbar et al reported an ionogel with excellent heat-induced self-healability by incorporating ion-dipole interactions into the system. 32 Dang et al utilized dynamic disulfide bonds to promote the reconstruction of the polymer network, resulting in the excellent and efficient self-healing performance of the ionogel, which guarantees the ionic conductor suitable for various functional applications. 33 The unique properties of ILs endow ionogel-based flexible sensors with advantages of chemical and thermodynamic stabilities, nonflammability, nonvolatility and high ionic conductivity.…”
Section: New Conceptsmentioning
confidence: 99%
“…It was reported that the ionic doping can even change the sign of the ionic Seebeck coefficient of the ionogels. For example, Liu et al found that doping EMIM:TFSI with Cl – can turn the ionic Seebeck coefficient changes from −4 to 17 mV/K (Figure d) . They attributed this change to the strong hydrogen bond between the Cl – and EMIM + . , As shown in Figure e, the peak assigned to C(2)–H underwent a chemical shift from 9.05 to 9.49 ppm with the increase of EMIM:Cl, which indicates the formation of a hydron bond.…”
mentioning
confidence: 91%
“…The addition of surfactant into ionogels can also affect the ionic Seebeck coefficient. Akbar et al added a fluorinated surfactant (FS-3100) into an ionogel made of 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMIM:OTf) and PVDF-HFP and observed the change of the ionic Seebeck coefficient from 6.1 to 27.3 mV/K when the FS-3100 loading was increased to 15 wt % . This surfactant effect is ascribed the interaction between the ethylene oxide groups of FS-3100 and EMIM + , which facilitates the thermal diffusion of EMIM + .…”
mentioning
confidence: 99%
“…Interestingly, the sensor showed very stable electronic signals under an extremely high temperature of 200 1C and extremely low temperature of À50 1C, suggesting its excellent high-and low-temperature resistance. 61,62 Additionally, the relative resistance-temperature response of the sensor based on 20%-Ionogel-1 from À50 1C to 200 1C is displayed in Fig. 7g.…”
Section: Ionogel-based Strain Sensor and Sensing Performance In The A...mentioning
confidence: 99%